Franchisees as Consumers Benchmarks, Perspectives and Consequences - Buchan, Jenny. (Springer New York : Imprint: Springer, 2013)
Franchising is an increasingly important global business model, but how well protected are franchisees the people who operate and make any franchise system really work? In this book, the author explores the many different roles that franchisees play in modern business, and their importance to the success of every franchise arrangement. As well as providing a comprehensive overview and analysis of the legal context of modern franchising relationships, and the different measures taken to deal with franchisee concerns, the author examines the weak links in contemporary franchising the areas where franchisees are rarely appropriately protected. Despite all the rhetoric, franchisees remain awkwardly accommodated within the law, and they are in need of attention through improved consumer protection, corporate governance, and business insolvency/bankruptcy laws. Franchisees As Consumers examines why franchisees remain more vulnerable under the law than employees and suppliers, and what can be done about it.